The Influence Of Computerized Systems On Employee Effectiveness (Case Study At The Mining And energy Office Of North Sumatra Province) - Yonta W Purba (IHSA Institute, 2020)
This study discusses the effect of computerized systems on employee work effectiveness. Where this computerized system helps to complete the work of employees properly, at the right time and can increase the effectiveness of employees' work.The formulation of the problem in this study is how the influence of a computerized system on the effectiveness of employees' work at the Mining and Energy Office of North Sumatra Province.The form of research in this thesis uses a quantitative research form with a sample of 32 respondents taken 32% of 100 employees at the Mining and Energy Office of North Sumatra Province.The results of this study prove that the computerized system has a positive effect on the effectiveness of employees' work. The effect of a computerized system on employee work effectiveness or 51.97% at the Mining and Energy Office of North Sumatra Province, this is based on r count greater than r table (0.9306 > 0.349) and has been explained in the previous chapter, and if the effect is interpreted to be in the moderate category.